Analisis Quality Of Service Management Bandwidth Pada Jaringan Internet Menggunakan Peer Connection Queue (Studi Kasus : Rumah Makan Ikan Ayam) - Candra Naya; Lathifah Zahroh (Jurnal SIGMA, 2021)
The The research objective was to analyze and implement network hotspots and bandwidth management at the Restaurant Ikan Ayam, so that the Restaurant can provide microtic-based hotspot facilities, evenly distribute bandwidth on hotspot networks to each customer and limit bandwidth usage according to the time stated on the voucher package. The research methods included the analysis method, namely by conducting a survey of the system that is running and the study of literature, the design method of network topology by selecting network devices to be used and configuration on each network device used, testing new networks, and maintenance activities (bandwidth traffic monitoring). The results of the research obtained are the implementation of the design of network hotspot topology and bandwidth management using RouterOS Microtics optimize the performance of hotspot networks and maximize bandwidth on hotspot networks. The conclusion of this study is that by using RouterOS Microtics on hotspot networks, internet cafes can limit the bandwidth usage of customers based on the voucher package that has been made and there is no attraction in attracting bandwidth between customers due to equal bandwidth distribution. Keywords: Hotspot, Bandwidth Management, RouterOS Microtics